Piety in a Secular Society: Migration, Religiosity, and Islam in Britain - Lewis, V; Kashyap, R (Wiley, 2013)
While in the American context religion is seen to facilitate immigrant incorporation by providing both spiritual and socioeconomic resources, in Europe high levels of religiosity are theorized as a barrier for immigrant incorporation into the secular mainstream. This is particularly salient for Islam, Europe's largest minority religion. In this study, we use the 2008–2009 England and Wales Citizenship Survey to compare levels and predictors of religiosity between Muslim and non‐Muslim first‐generation immigrants and their native‐born counterparts. Overall, Muslims are more religious than non‐Muslims. The results show that among non‐Muslims, the foreign‐born are significantly more religious than the native‐born; among Muslims, however, nativity has no impact on religiosity, indicating the native‐born are as highly religious as the foreign‐born. Additionally, although education is associated with reduced religiosity among non‐Muslim immigrants and native‐born, for Muslims it has no significant impact. Muslims across diverse ethnic and socioeconomic backgrounds show strong religious adherence. Results suggest that pathways to secular, mainstream norms do not operate in the same manner across Muslim and non‐Muslim immigrant groups.